2021
DOI: 10.1002/agj2.20509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different rice straw on soil microbial community structure

Abstract: Straw incorporation is an important measure to improve soil fertility and soil acidification. However, fresh straw that is returned to the field cannot be decomposed in a short time. Accumulation of undecomposed straw in the soil changes humus composition and the C structure. An experiment was designed to evaluate the effects of decomposed straw on soil fertility and microbial communities. Soil samples were collected from a rice-rice-tobacco region in southwestern China (The rice was Hongyou No 7, which was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
(44 reference statements)
2
17
0
Order By: Relevance
“…Across all treatments, Proteobacteria was the most dominant bacterial phylum, followed by Chloroflexi, Acidobacteria, and Nitrospirae, which is consistent with the findings of previous studies in paddy soils [ 61 , 62 ]. Proteobacteria is composed of numerous classes that are sensitive to copiotrophic conditions (K strategy), such as Beta- and Delta-proteobacteria [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…Across all treatments, Proteobacteria was the most dominant bacterial phylum, followed by Chloroflexi, Acidobacteria, and Nitrospirae, which is consistent with the findings of previous studies in paddy soils [ 61 , 62 ]. Proteobacteria is composed of numerous classes that are sensitive to copiotrophic conditions (K strategy), such as Beta- and Delta-proteobacteria [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…The abundance of Trichoderma may have increased, and the return of straw may have reduced the incidence of soil disease. However, the abundance of Trichoderma has a positive correlation with the content of nitrate nitrogen, the content of nitrate nitrogen has been increased, and maize absorption of nitrogen nutrients is promoted, leading to an increase in production (Liu et al 2021a;Vishwakarma et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Straw contains a large amount of nitrogen, phosphorus, potassium and other nutrients (Liu et al 2021a). The total amount of straw in China is signi cant, with the annual production of crop straw has exceeded 900 million tons (Shi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work showed that it is not the mutation pressure but other factors such as natural selection which plays a major role in shaping codon usage pattern. Liu, Ding, et al (2020) studied the effects of returning straw on the soil microbial community and found that returning straw increased soil organic C and that the analysis on the genera of soil microflora revealed that Pseudolabrys, Haliangium, Acidibacter, and Terracidiphilus were always dominant and played a significant role in straw decomposition. tested different ratios of sandstone and clay on the growth of potato and maize, and reported that compound soil ratios of 1:2 and 1:5 had the largest yield index and average yields.…”
Section: Research Areas Discussedmentioning
confidence: 99%